Penerapan Metode Proyek Untuk Meningkatkan Motivasi Belajar Pada Anak Usia 5-6 Tahun Di Raudhatul Athfal Lillah Kecamatan Tapung Kabupaten Kampar - Rayahu, Evi; Nikmah, Nikmah; Suliyani, Iis (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The purpose of this research was to obtain of the use of the project method in improving the early childhood aged 5-6 years sudents’ learning motivation through the project methods at RA Lillah. This research used classroom action research. The subjects in this study were 20 early childhood aged 5-6 years sudents, 9 boys and 11 girls. The resuls of the research proved that the early childhood aged 5-6 years sudents’ learning motivation at RA Lillah Tapung Kampar was low at 52.19% most of them got “poor” category at 51%-60%. After the implementation of the project method the early childhood aged 5-6 years sudents’ learning motivation improved in each Cycle at meetings 1 and 2, Cycle I was 65.31% in “Fairy good” category in range of 56%-75%. at meetings 1 and 2 of cycle II it was 84.68% in “good” category in range of 76%-100%. By the improvement of the early childhood aged 5-6 years sudents’ learning motivation each cycle I and II showed that this project method was effective to increase sudents’ learning motivation. The recommendation for the next researchers is expected to use other learning methods that are better and more effective and can also develop broader indicators of learning motivation so that the results can be better